How to change the world [videorecording (DVD)] - Rothwell, Jerry; Pepper, Barry, 1970- (Kino Lorber, 2016)
In 1971, a group of friends sailed into a nuclear test zone in a protest that would capture the public's imagination. That handful of individuals would go on to become the international environmental organization Greenpeace. Comprised of rare archival footage and interviews with former Greenpeace members, How to change the world recounts Greenpeace's early days under the pioneering helm of its founder Bob Hunter.